2017
DOI: 10.1111/ijd.13569
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol protects skin cells against inflammation, collagenolysis, apoptosis, and senescence caused by cigarette smoke damage

Abstract: BACKGROUND Pollution, especially cigarette smoke, is a major cause of skin damage. OBJECTIVES To assess the effects of the small molecule polyphenol, honokiol, on reversing cigarette smoke induced damage in vitro to relevant skin cells. METHODS Keratinocytes (HaCat) cultures were exposed to cigarette smoke and, after 48 hours, IL-1α and IL-8 were measured in cell supernatants. Moreover, TIMP-2 production, apoptosis rate, and senescence β-galactosidase expression were evaluated in primary human fibroblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 88 publications
(113 reference statements)
0
18
0
Order By: Relevance
“…Recently western medicine has begun to recognize its multiple pharmacological properties as an antioxidant (Dikalov et al, 2008 ), anti-inflammatory (Vaid et al, 2010 ), antiangiogenic (Fried and Arbiser, 2009 ), anticarcinogenic (Leeman-Neill et al, 2010 ; Mannal et al, 2011 ), and antibacterial (Park et al, 2004 ). Honokiol is known to reduce inflammation caused by ROS and was shown to protect HaCat keratinocytes and human fibroblasts against the damaging effects of cigarette smoke by reducing the inflammatory mediator IL1-α and degradation of collagen (Costa et al, 2017 ). The anti-inflammatory role was also shown to protect against UVR; in a mouse model honokiol significantly decreased UVB induced expression of inflammatory mediators including COX2, IL-1, and IL-6 (Vaid et al, 2010 ).…”
Section: Honokiol ( Magnolia Sp )mentioning
confidence: 99%
“…Recently western medicine has begun to recognize its multiple pharmacological properties as an antioxidant (Dikalov et al, 2008 ), anti-inflammatory (Vaid et al, 2010 ), antiangiogenic (Fried and Arbiser, 2009 ), anticarcinogenic (Leeman-Neill et al, 2010 ; Mannal et al, 2011 ), and antibacterial (Park et al, 2004 ). Honokiol is known to reduce inflammation caused by ROS and was shown to protect HaCat keratinocytes and human fibroblasts against the damaging effects of cigarette smoke by reducing the inflammatory mediator IL1-α and degradation of collagen (Costa et al, 2017 ). The anti-inflammatory role was also shown to protect against UVR; in a mouse model honokiol significantly decreased UVB induced expression of inflammatory mediators including COX2, IL-1, and IL-6 (Vaid et al, 2010 ).…”
Section: Honokiol ( Magnolia Sp )mentioning
confidence: 99%
“…Such cell lines can be keratinocyte cell lines, such as HaCaT or NHEK [47][48][49], or fibroblast cell lines, such as normal human foreskin-derived dermal fibroblasts (NHDF) [50,51]. These cells can be formed in a single layer or as a reconstructed skin model to create a more differentiated and accurate model of human skin characterized inner alia in the presence of the stratum corneum [40].…”
Section: In Vitro Efficacy Testingmentioning
confidence: 99%
“…Usually the cells are treated with the pollutant mixture, which consists of, e.g., particulate matter, urban dust, and heavy metals or cigarette smoke [39,48,50]. The impact of ozone or UV radiation can also be evaluated [38,39,47].…”
Section: In Vitro Efficacy Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms underlying the role of Hnk in cardioprotection have been reported, including the inhibition of oxidative stress and apoptosis (16), as well as improvement of autophagy (14) and mitochondrial function (13). In addition, a recent study revealed the association between Hnk and senescence in skin cells (17). However, to the best of our knowledge, it remains unknown whether inhibition of cardiomyocyte senescence is involved in the protective effect of Hnk on the heart.…”
Section: Introductionmentioning
confidence: 99%